2011
DOI: 10.1002/bit.23157
|View full text |Cite
|
Sign up to set email alerts
|

Application of magnetic particle tracking velocimetry to quadrupole magnetic sorting of porcine pancreatic islets

Abstract: Magnetic isolation is a promising method for separating and concentrating pancreatic islets of Langerhans for transplantation in Type 1 Diabetes patients. We are developing a continuous magnetic islet sorter to overcome the restrictions of current purification methods that result in limited yield and viability. In Quadrupole Magnetic Sorting (QMS) islets are magnetized by infusing superparamagnetic microbeads into islets’ vasculature via arteries that serve the pancreas. The performance of the islet sorter dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…In conclusion, a method has been researched for the simultaneous determination of particle count, particle diameter, and magnetophoretic mobility using dark-field videomicroscope velocimetry with image storage, processing, and analysis software using the commercial Hyperflux particletracking velocimeter (30). This study has demonstrated an available capability to analyze magnetic particles and cells that has been heretofore limited to only a handful of laboratories (15,18,24,(31)(32)(33)(34) with one-of-a-kind instruments. With correct operator-based settings, measurements of magnetophoretic mobility and particle count are robust, and diameter can be determined on the basis of calibration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, a method has been researched for the simultaneous determination of particle count, particle diameter, and magnetophoretic mobility using dark-field videomicroscope velocimetry with image storage, processing, and analysis software using the commercial Hyperflux particletracking velocimeter (30). This study has demonstrated an available capability to analyze magnetic particles and cells that has been heretofore limited to only a handful of laboratories (15,18,24,(31)(32)(33)(34) with one-of-a-kind instruments. With correct operator-based settings, measurements of magnetophoretic mobility and particle count are robust, and diameter can be determined on the basis of calibration.…”
Section: Resultsmentioning
confidence: 99%
“…Noncommercial instrumentation has been applied by specific investigators to the measurement of magnetophoretic mobility of individual particles and magnetically labeled cells by particle tracking velocimetry (17)(18)(19)(20). In certain cases, these measurements are directly applied to the establishment of parameters for the enrichment of magnetically labeled cells in flowing devices (21)(22)(23)(24) or to the quantification of cell surface markers (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…The QMS inlet flow rate (out of the buffer bag) was matched with the flow rate of tissue leaving the digest chamber to maintain a continuous purification process. The mechanism for the QMS process using this system is described in detail by Kennedy et al and others [15, 40, 54]. Briefly, as the tissue flow stream entered the QMS separator column, it is met with a parallel fresh stream of HBSS solution.…”
Section: Methodsmentioning
confidence: 99%
“…A specifically designed cell sorter capable of purifying cells labeled with magnetic nanoparticles is already available . This method has been described in the literature as quadruple magnetic sorting and has been successfully applied to several separation and purification applications for particles up to a size of 350 μm . To enable quadruple magnetic sorting for magnetic separation of encapsulated islets, the device must be adapted to work with a maximum particle size of 600 μm.…”
Section: Discussionmentioning
confidence: 99%